The Correlation Between Whatsapp Social Media Notification To The Results of Fasting Blood Sugar Level Control On The Participants of Prolanis Diabetes Mellitus Program at Graha Citra Husada Clinic - Lay Johan Gautama; Siti Nur Fatimah; Helni Mariani; Elsa Pudji Setiawati; Guswan Wiwaha; Insi Farisa Desy Arya (Syntax Corporation, 2022)
Diabetes mellitus is a degenerative disease that is often found in the practice of primary care, where cases are increasing. Lack of patient knowledge about pathophysiology, complications and management of cases of diabetes mellitus, thus making this case increase over time, as well as complications due to uncontrolled diabetes mellitus. Research Design is Quasi-Experimental with Pretest-Posttest one group design, which aims to examine the relationship between two variables, namely whatsapp social media notifications on fasting blood sugar control results. The results of the research on 46 subjects after the exclusion, 56.52% of subjects aged > 65 years (seniors), 56.52% female-type respondents, 50% high school educated, and 60.87% were retired. From sufficient test results about compliance relationship implementing the management on Whatsapp notification with fasting blood sugar level 7 days after notification using Chi-Square test obtained value P 0895. Based on this it can be concluded that there is no significant relationship between Whatsapp social media notifications on the 7th day fasting blood sugar level after notification. So to change behavior to be good behavior takes longer time and more intense counseling.